Resources dynamics from the point of view of the regenerated ornstein-uhlenbeck model - Figueira, João (2013)
We consider the problem of assessing resources dynamics in the context of an economic system subject to Gaussian consumption and deterministic productivity. A discrete time recursive equation is presented to justify the use of the Ornstein-Uhlenbeck diffusion process. Under assumptions about regeneration of the process, we observe the system equilibrium as to what concerns resources depreciation or accumulation